Feasibility of Recovering Energy from Municipal Solid Waste to Generate Electricity - Pasek, Ari Darmawan; Gultom, Kilbergen W.; Suwono, Aryadi (ITB Journal Publisher, LPPM ITB, 2013)
Population growth and economic development in Indonesia have increased the production of municipal solid waste (MSW) in many big cities, causing sanitary problems. The (MSW) disposal problem can be solved by applying an appropriate technology that can reduce the volume of the waste effectively and efficiently. Waste-to-Energy (WTE), or Energy-from-Waste (EFW), is one of the most effective and efficient technologies for reducing the waste volume. Energy recovered from the waste can be used for thermal or electricity generation. This paper deals with a feasibility study of utilizing MSW for generating electricity. A survey and investigation of waste characteristics, including waste composition, chemical and physical composition, and heating value, were carried out for typical Bandung MSW. An average heating value of 1500 kcal/kg can be expected from pre-treated MSW to be used as a fuel for direct combustion in a WTE plant. A typical design for a small-scale WTE plant is shown in this paper and also an energy analysis is provided. Approximately 800 kW of electric power can be generated from 50 tonnes of MSW per day.